Conductores de valor de la prensa digital con estrategias de pago por contenidos: análisis de caso del Financial Times, The Times y El Mundo en Orbyt (2013)
An analysis of value drivers has traditionally been absent from the core studies on value creation in Internet media. The purpose of this research is to shed a bit of light in this respect by analyzing three organizations with pay per content strategies: the Financial Times, The Times and The World in Orbyt.